2009
DOI: 10.1186/1472-6963-9-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of job rotation and role stress among nurses on job satisfaction and organizational commitment

Abstract: Background: The motivation for this study was to investigate how role stress among nurses could affect their job satisfaction and organizational commitment, and whether the job rotation system might encourage nurses to understand, relate to and share the vision of the organization, consequently increasing their job satisfaction and stimulating them to willingly remain in their jobs and commit themselves to the organization. Despite the fact that there have been plenty of studies on job satisfaction, none was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
1
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(159 citation statements)
references
References 48 publications
8
126
1
18
Order By: Relevance
“…Ho et al (2009) conducted a survey and state that stress has a negative effect on job satisfaction and commitment to the organization. On the other hand, they mention job rotation as an avoidance strategy used by nurses which had a positive effect on their job satisfaction and increased their commitment to the organization 26) . Burnard et al (2007) revealed that nursing students employed strategies like crying to decrease their stress and tolerate it better.…”
Section: Discussionmentioning
confidence: 99%
“…Ho et al (2009) conducted a survey and state that stress has a negative effect on job satisfaction and commitment to the organization. On the other hand, they mention job rotation as an avoidance strategy used by nurses which had a positive effect on their job satisfaction and increased their commitment to the organization 26) . Burnard et al (2007) revealed that nursing students employed strategies like crying to decrease their stress and tolerate it better.…”
Section: Discussionmentioning
confidence: 99%
“…Konflik interpersonal merupakan salah satu sumber yang menyebabkan seorang pegawai merasakan ketidakpuasan kerja terhadap pekerjaanya. Sejalan dengan ini, menurut Ho, et al (2009) bahwa kepuasan kerja adalah sikap positif atau negatif yang dimiliki seorang karyawan tentang pekerjaannya atau beberapa aspek spesifik pekerjaan, dan merupakan pandangan internal seorang individu. Karena itu, konflik interpersonal perlu untuk dikelola sehingga konflik dapat berdampak positif (konstruktif).…”
Section: Pengaruh Konflik Interpersonal Terhadap Kepuasan Kerjaunclassified
“…Por otro lado, diferentes estudios [28][29] evidencian que algunas de las dimensiones más valoradas por los profesionales sanitarios hacen referencia al apoyo y a la gestión directiva de los trabajadores de los centros de salud. También plantean la personalidad del trabajador como un elemento condicionante, lo que pone de manifiesto que la satisfacción de este colectivo está estrechamente vinculada con el soporte de las direcciones de recursos humanos de los centros de salud, hacia las necesidades concretas de cada uno de sus profesionales.…”
Section: Resulta Paradójico Que a Pesar Del Incremento De Estudios Dunclassified